2011
DOI: 10.1007/s00712-011-0253-5
|View full text |Cite
|
Sign up to set email alerts
|

Corruption, growth and ethnic fractionalization: a theoretical model

Abstract: This paper analyzes the existing relationship between ethnic fractionalization, corruption and the growth rate of a country. We provide a simple theoretical model. We show that a nonlinear relationship between fractionalization and corruption exists: corruption is high in homogeneous or very fragmented countries, but low where fractionalization is intermediate. In fact, when ethnic diversity is intermediate, constituencies act as a check and balance device to limit ethnically-based corruption. Consequently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…This result contradicts that of Cerqueti et al . (), who found that corruption levels, defined as the proportion of successful corrupt interactions in a case of a concession given for a new technology, are high in very fractionalized as well as in homogeneous but low in moderately fractionalized societies. Their results are guided by the assumption of two countervailing effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result contradicts that of Cerqueti et al . (), who found that corruption levels, defined as the proportion of successful corrupt interactions in a case of a concession given for a new technology, are high in very fractionalized as well as in homogeneous but low in moderately fractionalized societies. Their results are guided by the assumption of two countervailing effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a theoretical model, Cerqueti et al . () investigated the relationship between social fractionalization, corruption and growth. They find that corruption levels should be high in very fractionalized as well as in very homogeneous, but low in intermediately fractionalized societies (the opposite of Dincer's findings).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high correlation between government quality and economic development is, according to Treisman [42] Bby far the strongest and most consistent finding^in empirical work (see also [42,57,58]). We also control for ethnic fractionalization using the measure developed by Alesina et al [59], since more polarized societies are more prone to competitive rent seeking ( [60][61][62]: [63]) which may affect the quality of government institutions. Finally, the number of women in government may tap into both concepts since it may indicate a general inclusiveness of the political system [64][65][66].…”
mentioning
confidence: 99%